THE HISTORY AND IMPORTANCE OF THE STUDY OF TOPONYMICS IN LINGUISTICS - Khakimova Khurshida Bakhtiyarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the history of the emergence and study of toponymy, comments on the scientists and writers who conducted scientific research in this field and highlighted toponymic units in their scientific and artistic works. In addition, the importance of toponymy in the field of linguistics is analyzed.